2013
DOI: 10.12816/0017454
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Economic Development : Evidence from Nigeria

Abstract: Corruption has affected many countries all over the world especially the developing countries. It has various implications for both the developed and developing economies. Corruption hampers development and thus raises the level of poverty in any economy that finds itself entrenched in corrupt practices. Corruption creates uncertainty and risk in the growth and development potential of any country. The study investigated the impact of corruption on economic development in Nigeria. Secondary data were sourced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The outcome of this result, however, is not surprising going by many abandoned capital projects due to corruption. This result provides further empirical support to previous empirical studies that have also confirmed a declining impact of corruption on growth (Pellegrini and Gerlagh 2004, Mauro 1995, Akindele 2005, Adewale 2011and Nagari et al 2013.…”
Section: Interpretation and Discussion Of Resultssupporting
confidence: 87%
“…The outcome of this result, however, is not surprising going by many abandoned capital projects due to corruption. This result provides further empirical support to previous empirical studies that have also confirmed a declining impact of corruption on growth (Pellegrini and Gerlagh 2004, Mauro 1995, Akindele 2005, Adewale 2011and Nagari et al 2013.…”
Section: Interpretation and Discussion Of Resultssupporting
confidence: 87%
“…The data above suggest that majority of property developers in the study area subscribed to the fact that the cost of building materials is a major factor affecting property development in the study (Ibraheem et al 2013). Okenna (2020) found that the effect of corruption not only persisting property development but also on the economic development of the country.…”
Section: Analysis Of Factors Affecting Residential Property Developmentmentioning
confidence: 81%
“…Approval delays can impede project timelines, increasing costs and affecting business operations (Morisset & Lumenga-Neso, 2002). Corruption remains a pervasive challenge in Nigeria's business environment (Amadi & Alapiki, 2012;Ibraheem, Umar, & Ajoke, 2013). Businesses may encounter demands for bribes or kickbacks when dealing with regulatory authorities, customs, or law enforcement agencies.…”
Section: Regulatory Compliance In Nigeriamentioning
confidence: 99%

A Review on Data-Driven Regulatory Compliance in Nigeria

Bisola Beatrice Oguejiofor,
Adedolapo Omotosho,
Kehinde Mobolaji Abioye
et al. 2023
Int. j. appl. res. soc. sci.